The effects of Sijunzi decoction-supplemented cat food on physiological parameters and gut microbiota in healthy adult cats - Liu, Wei; Chen, Yinghao; Ma, Mingyu; Liu, Biao; Li, Jiayin; Zhou, Yang; Yu, Junkun; Lin, Jiahao (Frontiers in Veterinary Science, 2025)
Cats have unique digestive characteristics that make them prone to gastrointestinal disorders, creating a growing demand for functional diets that support digestive and immune health. Traditional Chinese medicine (TCM) offers recognized advantages in gastrointestinal protection, yet its application in cat food remains rare. Among TCM formulas, Sijunzi Decoction (SJZD) has demonstrated benefits in enhancing appetite and protecting the intestine, yet its application in companion animal nutrition remains unexplored. In this study, we developed a kind of novel functional cat food that support intestinal health and immunity by incorporating the four constituent herbs of SJZD into the daily diet of healthy adult cats and assessed its effects on physiological parameters and gut microbiota in healthy adult cats. We displayed that a quality control system to ensure product consistency was successfully established. Further, we found that SJZD-supplemented cat food could promote digestion and nutrient absorption of cats, strengthens immune and antioxidant defenses of cats, and contribute to reducing the risks of obesity and inflammatory bowel disease of cats. In a word, this work provides both scientific evidence and a novel nutritional approach for improving feline health, while expanding the potential clinical applications of SJZD.